Mat dari Serbuk Daun Zodia (Evodia suaviolens) sebagai Pengendali Nyamuk Aedes aegypti - Yulianto Sri Wahyu Nugroho; Purwanto Purwanto; Agus Kharmayana Rubaya (Poltekkes Kemenkes Yogyakarta, 2009)
Indonesia is a tropical country rich with natural resources which can be used in supporting environmental health efforts. One of the plants which characterized as mosquito repellent is Zodia, of which mat formed mosquito essence can be made. The advantages of using such mat are lowering the risk of being bite by mosquito vectors and is has no side effect. The study was aimed to understand the ability of Zodia leaves powder mat in fainting and killing Aedes aegypti mosquitos. The study was an experiment with post-test only with control group design. The data was statistically analyzed by using Probit analysis from Compustat software and One-way Anova and LSD tests from SPSS software on 95% significance level. The results showed that for the three various powder weight (i.e. 1, 2, and 3 gr) the LD50 were 1,18; 0,85, and 0,70 respectively; whereas the KT50 were 14’ 19,2”; 7’ 40,8”, and 5’ 21”, respectively. Further tests also showed that the mosquito mortality amongst the treatments were statistically different, and 3 gram Zodia’s powder was the most effective. It wasadvised that advanced research should be conducted to study the durability of the mat, as well as it’s killing ability against other mosquito vector species.